The Timing of Choice-Enhancing Policies - Takeshi Murooka; Marco Schwarz (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2017)
Recent studies investigate policies motivating consumers to make an active choice as a way to protect unsophisticated consumers. We analyze the optimal timing of such choice-enhancing policies when a firm can strategically react to them. In our model, a firm provides a contract with automatic renewal. We show that a policy intending to enhance consumers choices when they choose a contract can be detrimental to welfare. By contrast, a choice-enhancing policy at the time of contract renewal increases welfare more robustly. Our results highlight that policies should be targeted in timing to the actual choice inefficiency.
Keywords: D03; D18; D21; D40; L51; 330; active choice; automatic renewal; automatic enrollment; procrastination; consumer naivete; present bias